AIDS and non AIDS-related malignant lymphoma in Tanzania - Kaaya, Ephata E (Makerere Medical School, 2006)
BACKGROUND: Malignant lymphoma (ML) in HIV patients, are second in frequency to Kaposi's sarcoma (AKS) as AIDS-defining tumors. In Africa the frequency of AIDS-related lymphoma (ARL) is rare and the findings are controversial. Kaposi's sarcoma (KS) lesions are now causally associated with KSHV/HHV-8 but whether African ARL shows this association is not clear. METHOD: Cancer registry data was reviewed for retrospective cases. Both retrospective and prospective lymphoma cases were classified according to the revised European-American (REAL) classification. Immunephenotyping was performed on both frozen and fixed paraffin sections. Viral DNA was assessed by polymerase chain reaction (PCR) of formalin fixed or frozen biopsies. In situ hybridization (ISH) was used to determine the presence of EBV encoded RNA (EBER). OBJECTIVES: To determine the frequency and type of AIDS and non-AIDS related malignant lymphoma in Tanzania and a possible co-association with KSHV/HHV-8 and EBV. RESULTS: An overall increasing tendency for ML in Tanzania was observed during 1991–94 and a clear increase from 1993. The tumors were classified as Burkitt's (6), diffuse large cell (10), precursor-B lymphoblastic (1) and Hodgkin's disease (5) from HIV positive and negative patients. Ten (40%) high grade ML and three Hodgkin's lymphoma from HIV patients had HHV-8 DNA. These findings were not related to age, sex or type of lymphoma. There was no association of HHV-8 with the lymphoma cells. Epstein-Barr virus (EBV) was demonstrable in most (13/18; 72%) of the tested tumors and seven (31.8%) had both HHV-8 and EBV. CONCLUSIONS: This study suggests an overall increased frequency of ML patients infected with HHV-8 in Tanzania particularly in HIV patients which may result from the well established high HHV-8 prevalence in the general population, but HHV-8 was not associated with ARL pathogenesis as reflected by lack of tumor cell infection. As opposed to EBV, measures targeting HHV-8 for control of ML may therefore not be appropriate. RUNNING TITLE: HHV-8 and EBV in Tanzanian malignant lymphoma.